(untitled) (Takwil: Journal of Quran and Hadith Studies, 2022)
The development of exegesis covered the ideology of the interpreter which is influenced by education, the sect adopted and the environment that surrounds the interpreter. The belief held by the commentator is then turned into a truth which sometimes blames other interpretations. The ideology of this interpretation can be found when Islam had developed during the tabi’in period, namely when a period of the emergence of various works of interpretation with the style of Sufism, theology, fikh, linguistics and so on. This ideological interpretation is then seen by contemporary commentators as a weakness of the previous interpretation. This study reveals various arguments from contemporary commentators regarding the methodology of interpretation, the ideology of interpretation to the subjectivity of previous commentators. This methodological criticism by contemporary experts is formulated in several important points as recommendations for the present.